2016
DOI: 10.1007/s11095-016-1941-1
|View full text |Cite
|
Sign up to set email alerts
|

N-acetylcysteine Protects Mice from High Fat Diet-induced Metabolic Disorders

Abstract: Purpose To study the effects of N-acetylcysteine (NAC, C5H9NO3S) on diet-induced obesity and obesity-related metabolic disorders. Methods Six-week-old male C57BL/6 mice fed a chow or high-fat diet (HFD) were treated with NAC (2 g/L) in drinking water for 11 weeks. Its influences on body weight, and food intake were manually measured and on body composition were analyzed by magnetic residence imaging. Glucose meter and ELISA were used to determine serum glucose and insulin levels, and lipid content in the liv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

10
44
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(61 citation statements)
references
References 38 publications
10
44
0
Order By: Relevance
“…The administration of the antioxidant NAC did not significantly alter the body weight of these animals. On the other hand, when NAC was administered concomitantly to the high fat diet, Ma et al, (22) observed a reduction in body weight of the Group Treated with NAC, as compared to the non-treated obese group.…”
Section: ❚ Discussionmentioning
confidence: 99%
“…The administration of the antioxidant NAC did not significantly alter the body weight of these animals. On the other hand, when NAC was administered concomitantly to the high fat diet, Ma et al, (22) observed a reduction in body weight of the Group Treated with NAC, as compared to the non-treated obese group.…”
Section: ❚ Discussionmentioning
confidence: 99%
“…Ma et al . () reported decreases in epididymal and subcutaneous white adipose tissue, as well as decreased adipocyte expansion in brown adipose tissue and evidence of altered thermogenic gene expression suggesting increased energy expenditure following chronic NAC supplementation. Interestingly, however, notwithstanding changes culminating in altered body composition, Ma et al .…”
mentioning
confidence: 97%
“…Interestingly, however, notwithstanding changes culminating in altered body composition, Ma et al . () reported that NAC supplementation at 2% in the drinking water for 11 weeks beginning at 6 weeks of age did not affect body mass at any time point, whereas Cao & Picklo () observed that 1 g kg −1 NAC in the diet decreased body mass after 5 weeks of supplementation, although the effects were modest after 17 weeks of supplementation. It was also previously reported that NAC supplementation decreased body mass in a dose‐dependent manner (Kim et al .…”
mentioning
confidence: 99%
“…Accumulating experimental evidence indicated that NAC promoted adiponectin gene expression, resulting in reduced hyperglycemia and hyperinsulinemia, and amelioration of IR [21,26]. The principal mechanisms by which adiponectin improve insulin sensitivity seems to be through augmented fatty acid oxidation and suppression of hepatic glucose production [24].…”
Section: Discussionmentioning
confidence: 99%